Review of Current Morphometric Standards in Craniosynostosis. Issue 2 (June 2022) - Kreinces, Jason; DeSimone, Joseph; Graifman, Gillian; Zellner, Elizabeth
Background/Purpose: In craniosynostosis, diagnostic imaging is crucial for identifying skull abnormalities, planning for surgical correction, and post-operative and follow-up evaluations. However, classifying postoperative corrected skull morphology is a highly subjective task for all craniofacial surgeons. Initially, many surgeons utilized the Whittaker categorization test as the post-operative outcome measure, which is based on the subjective esthetic appearance as determined by the surgeon, patient, and patient's family. While the advancement of 3D imaging and anthropometric measurements techniques has allowed various research groups to produce normative skull models to serve as treatment guides, it is still difficult to determine the objective morphological standard. The purpose of this study is to review the current standards for classifying normal skull morphology. Methods: This paper is a review of the current surgical standards of normal cranial morphology. A systematic literature review following PRISMA guidelines was performed; all published studies over a 40-year period from 1980 to 2020 were reviewed that assessed cranial morphology of healthy pediatric samples. Results: A review of the strategies utilized by some of the major medical device manufacturers in craniosynostosis correction surgery is presented. Many of these companies have progressed to using 3D normative skull construction and 3D surface analysis to measure cranial morphology. However, many variations remain among industry standards. Conclusion: Normative head shapes and cohort data matched to similar population groups have a crucial function in the diagnosis, pre-operative planning, and post-operative evaluations in craniofacial surgery. However, industry standards for "normal head shape" utilized in surgical analysis and planning remain diverse and can be somewhat opaque to the craniofacial community. Despite the advancement of 3D imaging techniques, most reported outcomes following craniofacial surgical interventions are still subjectively defined.